2016
DOI: 10.1002/ajmg.a.37677
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical analyses with neuropsychological assessment of a case of del(10)(q26.2qter) without intellectual disability: Genomic and transcriptomic combined approach and review of the literature

Abstract: Terminal deletion of the long arm of the chromosome 10 is a rare but well known abnormality, with a large phenotypic variability. Very few data are available about subtelomeric deletion 10q26 patients without intellectual disability. Herein, we report the case of a young adult with a classical 10q26.2qter deletion. She exhibited mainly short stature at birth and in childhood/adulthood without intellectual disability or behavioral problems. After clinical and neuropsychological assessments, we performed genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Moreover, several cases of 10q deletions without intellectual disability have been reported. 24 All these data seem refusing the hypothesis that DOCK1 can be a dosage-sensitive gene. 24 The hypothesis of a possible gene dosage effect, that could explain the presence of symptoms such as developmental delay or cognitive impairment, autism, epilepsy, or brain malformations, has never been experimentally assessed in the context of 10q26 duplication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several cases of 10q deletions without intellectual disability have been reported. 24 All these data seem refusing the hypothesis that DOCK1 can be a dosage-sensitive gene. 24 The hypothesis of a possible gene dosage effect, that could explain the presence of symptoms such as developmental delay or cognitive impairment, autism, epilepsy, or brain malformations, has never been experimentally assessed in the context of 10q26 duplication.…”
Section: Discussionmentioning
confidence: 99%
“…24 All these data seem refusing the hypothesis that DOCK1 can be a dosage-sensitive gene. 24 The hypothesis of a possible gene dosage effect, that could explain the presence of symptoms such as developmental delay or cognitive impairment, autism, epilepsy, or brain malformations, has never been experimentally assessed in the context of 10q26 duplication. The mild phenotype that was reported in a 11 years old presenting with a moderate intellectual disability and no major malformations and carrying a 10q26!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen OMIM genes are underlined to be morbid genes from DECIPHER database in case of 10q26.12qter deletion (Table 2 ). Several compelling studies reported that interstitial deletion at 10q26.2q26.3 or terminal 10q26.2 deletion only caused mild neurocognitive phenotypes or minor dysmorphic features with near normal development and intellect [ 20 23 ]. Therefore, we speculate that the deleted genes located at 10q26.12q26.13 ( OAT , ACADSB, IKZF5, HTRA1, ARMS2, FGFR2 and WDR11 ) are responsible for those notable malformations.…”
Section: Discussionmentioning
confidence: 99%